Negotiating Islamic Values and Human Rights: Community Responses to Same-Sex Marriage Legalization among Patani Muslims in Southern Thailand - Sureeyana Masae; Raharjo; Ema Hidayanti (JPI: Jurnal Pustaka Indonesia, 2025)
This study examines how Muslim actors in the Patani region of Southern Thailand negotiate Islamic values and human rights principles in responding to the legalization of same-sex marriage. Using an interpretivist qualitative multiple-case study design, the research involved seven purposively selected informants across Yala, Pattani, and Narathiwat, comprising three heads of Islamic religious councils, two students, one teacher, and one community activist. Data were generated through in-depth unstructured interviews, participatory observation, and document analysis, and were analyzed through iterative coding, thematic categorization, cross-case comparison, and interpretive synthesis, with credibility strengthened through source and methodological triangulation. The findings indicate a pattern of normative negotiation rather than a simple acceptance-rejection dichotomy. Participants generally maintained the Islamic normative position that same-sex marriage is not religiously valid, while distinguishing this theological judgment from the civic treatment of individuals. They simultaneously emphasized human dignity, security, legal protection, freedom from violence, and peaceful coexistence, while recognizing the state’s authority to regulate civil law. Responses were shaped by religious education, ulama authority, Patani Malay cultural identity, educational background, and exposure to digital and transnational human-rights discourse. The study contributes the concept of normative religious non-acceptance with civic accommodation to explain how religious commitment and minority citizenship may coexist without requiring normative homogenization.